From private office to civil service department: cultural change in the Lord Chancellor's Department 1970–1986. Issue 1 (2nd January 2021) - Mulcahy, Linda; Rowden, Emma
ABSTRACT: A considerable amount of literature exists on the office of the Lord Chancellor and the unique role of the holders of this office played in the British constitution for many hundreds of years. However, hardly any research has been undertaken on the civil servants that worked in the Lord Chancellor's Office and the way in which they assisted the navigation of a difficult path between matters pertaining to the legislative, executive and judicial branches of government. Drawing on an extensive review of the archives relating to the Courts Act 1971, this article draws attention to the elite band of lawyers who made up the office and the ways in which their scant knowledge of the administration of justice was exposed in the corridors of Whitehall in the years that followed this Act coming into effect. The events we describe are of particular interest because they occurred away from the public gaze, behind the scenes in Whitehall and because they represented a transformation of the role of the office from policy makers to service providers.